AB0334 Very high titer of anti-citrullinated protein antibodies is associated with the achievement of clinical remission by abatacept in biologic-naïve patients with rheumatoid arthritis (the abroad study). (23rd January 2014) - Fujii, T.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Hashimoto, M.; Ohmura, K.; Yamamoto, A.; Nakahara, H.; Maeda, K.; Yokota, A.; Miki, K.; Shimmyo, N.; et al.
Abstract : Background: The therapeutic goal of rheumatoid arthritis (RA) is clinical remission. However, patient characteristics associated with clinical remission by abatacept (ABT) are little known. Objectives: The aim of this study is to determine the predicting factors of clinical remission induced by ABT in biologic-naïve RA patients. Methods: The ABROAD (ABatacept Research Outcome as a first-line biological Agent in the real worlD) study is an ongoing prospective multicenter cohort study for investigating the efficacy and safety of ABT for treating biologic-naïve RA in the west side of Japan. Baseline profiles of the enrolled 155 RA patients (female = 83.2%, mean age at the ABT initiation = 61.3 years old, and disease duration = 8.1 years) and simplified disease activity index (SDAI) remission rate at 24 weeks were examined and then clinical factors associated with remission were determined. Anti-citrullinated protein antibodies (ACPA) titers at baseline were classified into 4 groups; negative (less than the upper limit of normal [ULN], <4.5IU/mL), low-positive (less than 3 times of the ULN, 4.5-13.5 IU/mL), high-positive (less than 22 times of the ULN, 13.6-99 IU/mL), and very high-positive (equal or more than 22 times of the ULN, >=99 IU/mL). Results: SDAI remission (<3.3) was achieved in 16% of our patients. Short disease duration (<1 year) (Odds ratio [OR] = 2.79, 95% confidence interval [CI] = 1.02-7.61, p = 0.045), and very high-positive ACPA (OR = 4.44, 95% CI = 1.28-15.38, p = 0.019) were significantly associated with clinical remission at 24weeks. Also, low disease activity defined by DAS28-CRP (<2.7) at baseline (OR = 4.97, 95% CI = 0.97-25.4, p = 0.054) and male gender (OR = 2.76, 95% CI = 0.91-8.40, p = 0.072) appeared to be linked with SDAI remission. However, age at ABT initiation, concomitant use of methotrexate, CRP level at baseline, and the 1987 ACR criteria fulfillment were not statistically associated with SDAI remission. Although ACPA positivity was associated with a better response to ABT in the ORA registry (ref.), our data demonstrated that low- or high-positive ACPA was not determined as the predicting factor for remission. Conclusions: Biologic-naïve RA patients with disease duration less than 1 year and very high-positive ACPA can achieve SDAI remission by ABT more frequently than without, suggesting that T cells play a critical role in synovial inflammation in such patients. References: Gottenberg JE, et al. Ann Rheum Dis 2012;71:1815. Disclosure of Interest: T. Fujii Grant/research support from: Bristol-Myers Squibb Japan, M. Sekiguchi Grant/research support from: Bristol-Myers Squibb Japan, K. Matsui Grant/research support from: Bristol-Myers Squibb Japan, M. Kitano Grant/research support from: Bristol-Myers Squibb Japan, M. Hashimoto Grant/research support from: Bristol-Myers Squibb Japan, K. Ohmura Grant/research support from: Bristol-Myers Squibb Japan, A. Yamamoto Grant/research support from: Bristol-Myers Squibb Japan, H. Nakahara: None Declared, K. Maeda: None Declared, A. Yokota: None Declared, K. Miki: None Declared, N. Shimmyo: None Declared, T. Kuroiwa: None Declared, K. Murakami: None Declared, Y. Ozaki: None Declared, K. Higami: None Declared, I. Yoshii: None Declared, Y. Nozaki Grant/research support from: Bristol-Myers Squibb Japan, T. Ikawa: None Declared, S. Morita: None Declared, Y. Kawahito Grant/research support from: Bristol-Myers Squibb Japan, N. Nishimoto Grant/research support from: Bristol-Myers Squibb Japan, T. Mimori Grant/research support from: Bristol-Myers Squibb Japan, H. Sano Grant/research support from: Bristol-Myers Squibb Japan